Underrepresentation of Local Researchers in Geophysical Studies at the Bosumtwi Impact Crater: Insights from A Systematic Review - Boateng, Cyril D.; Akrugu, Christopher A.; Wemegah, David D.; Danuor, Sylvester K. (Scientific African, 2024)
This article is published in Scientific African 21 (2023) e01893; https://doi.org/10.1016/j.sciaf.2023.e01893